Information Security Management Handbook, Fifth Edition, Volume 3 - Tipton, Harold (CRC Press, 2009)
Since 1993, the Information Security Management Handbook has served not only as an everyday reference for information security practitioners but also as an important document for conducting the intense review necessary to prepare for the Certified Information System Security Professional (CISSP) examination. Now completely revised and updated and in its fifth edition, the handbook maps the ten domains of the Information Security Common Body of Knowledge and provides a complete understanding of all the items in it. This is a must-have book, both for preparing for the CISSP exam and as a comprehensive, up-to-date reference.